Activities of the National economic councils (1957–1964): organizational impasse or the possibility of a breakthrough - A. R. Gapsalamov (Вестник Майкопского государственного технологического университета)
The presented research touches upon the issues of the emergence, functioning and liquidation of economic councils. The article shows the main reasons that signaled the beginning of the structural decentralization of the management system, as well as the factors that caused the reverse process.The methodological basis of the presented research is an approach based on the use of the historicism principle. It allows us to analyze historical stages in accordance with the specific historical situation in their dialectical interconnection and conditionality. The application of the historicism principle requires the study of any component of the historical process in its development. Guided by this principle, the author sought to show the transformation of the industrial management system of the USSR in 1957–1964. The principle under consideration was used in conjunction with the methods of scientific knowledge. In his research, the author used such general scientific research methods as analysis, synthesis, deduction and abstraction.The relative effectiveness of the obtained reforms has been shown. At the same time, structural changes in the management system could not give an explosive character to the growth of the industrial sector. The reasons for the curtailment of economic councils lay not only in voluntarism or organizational problems, but in the absence of a single system of decentralized management. Under the slogans of territorial administration, in real practice, sectoral centralized administration was preserved. In addition, the system itself, being inert throughout the reforms, followed the path of strengthening departmental-sectoral management.